The level of psychological adaptation of male and female adolescent to physical activity - كرميش , نادية آمال (sports creativity, 2025)
The level of psychological adaptation of male and female adolescent to physical activity , this study deal with an aspect of the important aspects of an individual’s life , in order to preserve . it is considered the main axis for self promotion and satisfying its needs especially among adolescents as it aimed to know the level of psychological adaptationamong adolescents in psychological activity and the reveal the differentes between pratctitioners and non practitioners , it also aimed to reveal the differences in psychological adjustment between the sexes where the number of the sample reached 130 male and female students their agges ranged between 15 and 16 and they were chosen randomly , the children’s psychological adaptation scale was applied to them as it is an important factor in their personal stability and their social interaction with others , in their study we used the desprictive approach to address the subject , among the findings of the study are the following : - The level of psychological adaptation of adolescents to physical activity is high in - There are no differences in self adaptation accordings to the sex variable in physical activity - There are no differences in adaptation between practitioners and no practitioners in physical activity